2018
DOI: 10.5505/ktd.2018.58815
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of hypophyseal fossa related structure; in terms of surgical approach

Abstract: Ce er rr ra ah hi i y ya ak kl la aş şı ım m a aç çı ıs sı ın nd da an n h hi ip po of fi iz ze er r f fo os ss sa a i il le e i il li iş şk ki il li i y ya ap pı ıl la ar rı ın n m mo or rf fo om me et tr ri ik k a an na al li iz zi i M Mo or rp ph ho om me et tr ri ic c A An na al ly ys si is s o of f H Hy yp po op ph hy ys se ea al l F Fo os ss sa a R Re el la at te ed d S St tr ru uc ct tu ur re e; ; i in n T Te er rm ms s o of f S Su ur rg gi ic ca al l A Ap pp pr ro oa ac ch h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is important to determine the detailed characteristics of hypophysis due to the presence of surrounding vital structures and its anatomic location. There are various studies about hypophysis via advanced imaging techniques (14)(15)(16)(17)(18)(19). However, in the literature, no study was found in which the topography of the gland was detected in cavum cranii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to determine the detailed characteristics of hypophysis due to the presence of surrounding vital structures and its anatomic location. There are various studies about hypophysis via advanced imaging techniques (14)(15)(16)(17)(18)(19). However, in the literature, no study was found in which the topography of the gland was detected in cavum cranii.…”
Section: Discussionmentioning
confidence: 99%
“…Uzun et al (17), analyzed the surgical corridors in operations by determining the morphometric analysis of the structures associated with fossa hypophysialis for surgical approaches and determining safe distances in surgical operations related to the skull base. In the present study, it was aimed to determine the topography of the hypophyseal region in cavum cranii and to figure out the regional anatomy better.…”
Section: Discussionmentioning
confidence: 99%